Industrial training report: Universiti Tun Hussein Onn Malaysia (UTHM) / Luqman Hakim Alias - Alias, Luqman Hakim (Faculty of Business and Management, 2025)
Universiti Tun Hussein Onn Malaysia (UTHM) is one of the public universities in Malaysia that offered services such as academic programs, intellectual property management, consultancy service regarding business, contract research service and many more. This organization have 2 branch which are UTHM Main Campus Branch and the another one is UTHM Pagoh Campus Branch. For the six month period during my final year, I got the opportunity to do my industrial training at Universiti Tun Hussein On Malaysia (UTHM) Main Campus Branch. I was assigned to the Human Resource Department. Within this department, I have been exposed to the real situation in working industry. As the task and responsibilities during my internship, I was assigned to learn and help to manage various job like handling employees retirement process, managing employee salaries and allowance, managing the process of employee making loan, managing the employee leave and also help to rearrange various confidential document that related to UTHM employees. Besides that, I am also got the opportunity to help on managing the employees recruitment process besides managing the process of dispose the old files. Other than that, I am also was assigned to help in managing all the business at the service counter and many more. During my industrial training period, I am also got assigned to be involved in some major projects like Convocation and Employee Retirement Ceremony. From my industrial training period, it had gave me the chance to gain various experience that quite useful for my future career. Furthermore, it also has enhance my skills especially in terms of my interpersonal skills and communication skills which allow me to interact with the employees at all levels besides make a contribution to the department's overall effectivene